2020
DOI: 10.1080/10717544.2019.1710622
|View full text |Cite|
|
Sign up to set email alerts
|

Synergism of cisplatin-oleanolic acid co-loaded hybrid nanoparticles on gastric carcinoma cells for enhanced apoptosis and reversed multidrug resistance

Abstract: Combined administration of different drugs is a widely acknowledged approach for effective cancer therapy. However, the limited targeting, as well as inferior drug loading capacities of current drug delivery systems (DDS), are still the bottleneck for better performance in cancer treatment. Herein, we successfully developed a cancer cell membrane (CM) decorated calcium carbonate (CC) hybrid nanoparticles (HN) for the co-delivery of cisplatin (CDDP) and oleanolic acid (OA). The physicochemical property of HN/CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The HNs were prepared from the membrane of MGC-803 cancer cells mixed with an aqueous solution of calcium carbonate (CC). The binding between calcium ions and the phosphates of the membrane led to the improved stability and targeting of the DDS [ 79 ]. Cisplatin is a commonly used chemotherapeutic agent involved in the formation of DNA adducts, which leads to DNA damage and apoptosis induction in cancer cells [ 80 ].…”
Section: Nanoformulations With Pentacyclic Triterpenoids In Anticamentioning
confidence: 99%
See 1 more Smart Citation
“…The HNs were prepared from the membrane of MGC-803 cancer cells mixed with an aqueous solution of calcium carbonate (CC). The binding between calcium ions and the phosphates of the membrane led to the improved stability and targeting of the DDS [ 79 ]. Cisplatin is a commonly used chemotherapeutic agent involved in the formation of DNA adducts, which leads to DNA damage and apoptosis induction in cancer cells [ 80 ].…”
Section: Nanoformulations With Pentacyclic Triterpenoids In Anticamentioning
confidence: 99%
“…The drug release profile, in the case of both compounds, was pH-dependent, which is a crucial aspect in anticancer strategy due to the acidic extracellular pH in cancer tissue. Tumor-specific drug targeting and accumulation with the intensification of apoptosis processes and the withdrawal of MDR cells in both the in vitro and in vivo conditions of experiment were observed [ 79 ].…”
Section: Nanoformulations With Pentacyclic Triterpenoids In Anticamentioning
confidence: 99%
“…So, we precisely controlled the shapes and sizes of the NPs. In recent studies, the NPs sizes prepared were in the range of 100–600 nm 36 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have prepared calcium carbonate (CC) hybrid nanoparticles (HN) decorated with cancer cell membranes (CM) for the delivery of cisplatin (CDDP) and OA. The results showed that compared to free drugs alone or mono systems, it could enhance cell apoptosis and can reverse the cancer cells multidrug resistance [ 33 , 34 ].…”
Section: Pharmacological Effects Of Oa and Its Derivativesmentioning
confidence: 99%